Follicular Dynamics and Endocrine Profile during Normal Estrous Cycle and Early Pregnancy in Surti Buffaloes - Chaudhari, Dinesh V.; Panchal, Mahesh T.; Dhami, Arjan J.; Sarvaiya, Nitesh P.; Pathan, Mohsinkhan M.; Hadiya, Kamlesh K.; Patel, Jagdish A. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted on Surti buffaloes for follicular dynamics and endocrine profile during normal estrous cycle (n=6) and early pregnancy (n=6). In cyclic and early pregnant buffaloes, one-wave (33.33% vs. 50.00%) and two-waves (66.66% vs. 50.00%) follicular development was recorded, without three-wave pattern. In cyclic buffalo, the length of estrous cycle and duration of inter-ovulatory interval were little shorter in one wave cycles than in two wave cycles (22.50±0.50 and 23.25±0.25 days). The number of follicles differed non-significantly within and between cyclic and early pregnant buffaloes. The mean maximum diameter of dominant follicle of second wave was significantly larger in cyclic than early pregnant animals for two wave pattern (1.09±0.02 vs 0.73±0.02 cm). In cyclic buffaloes, the mean maximum CL size recorded was 1.21±0.02 and 1.52±0.05 cm (P
Keywords: Buffalo; Early pregnancy; Estrous cycle; Endocrine profile; Follicular dynamics